2017
DOI: 10.2527/jas2017.1730
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effects of early gestation in utero heat stress on postnatal fasting heat production and circulating biomarkers associated with metabolism in growing pigs

Abstract: The study objective was to characterize effects of early gestation in utero heat stress (IUHS) on postnatal fasting heat production (FHP) and blood biomarkers associated with metabolism in growing pigs. Based on previous observation of increased postnatal core body temperature set point in IUHS pigs, we hypothesized that FHP would be altered during postnatal life because of IUHS. Pregnant first-parity gilts were exposed to thermoneutral (TN; = 4; 17.8 ± 0.1°C) or heat stress (HS; = 4; cyclical 28 to 38°C) cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In utero hypothalamic-pituitary-adrenal axis programming also occurs in pigs (47). When in utero heat stressed pigs are exposed to postnatal stressors [i.e., handling, (48) or heat insult, (49)] they have higher cortisol concentrations and increased core temperature, respectively. It has been established that the immune system has lower priority in fetal nutrient partitioning than other systems, such as the nervous system and brain (50) which might explain the programming effect of systems regulated at the brain level (i.e., cortisol regulation and thermoregulation).…”
Section: Fetal Programming and Heat Stress-induced Alterations In Celmentioning
confidence: 99%
“…In utero hypothalamic-pituitary-adrenal axis programming also occurs in pigs (47). When in utero heat stressed pigs are exposed to postnatal stressors [i.e., handling, (48) or heat insult, (49)] they have higher cortisol concentrations and increased core temperature, respectively. It has been established that the immune system has lower priority in fetal nutrient partitioning than other systems, such as the nervous system and brain (50) which might explain the programming effect of systems regulated at the brain level (i.e., cortisol regulation and thermoregulation).…”
Section: Fetal Programming and Heat Stress-induced Alterations In Celmentioning
confidence: 99%
“…The concentration of total triiodothyronine (T3) and total thyroxine (T4) in maternal and fetal serum were determined using commercially available RIAs (MP Biomedical, Irvine, CA, USA) for each analyte, which have previously been used with porcine samples [20]. Assays were conducted in duplicate in accordance with the manufacturer's directions with the exception that both samples and standards were diluted 1 in 4 prior to T4 assay to effectively reduce sample viscosity and thereby improve assay performance.…”
Section: Serum Total T3 and T4mentioning
confidence: 99%
“…Feed restriction for as little as 24 h has been shown to cause a significant decrease in the circulating T3 and T4 levels in swine [28]. There is also established interplay between feed intake and ambient temperatures [20,29,30] as well as additional alterations following adaptation to new diets [31]. Given that the control and infected gilts originated from the same genetic nucleus farm, the apparent susceptibility of the thyroid hormone system to environmental conditions leads us to posit that the observed pre-challenge difference likely stems from minor differences in the conditions between the facilities in which these two groups were housed.…”
Section: Figure 5 Fetal Gene Expression Associated With Regulation Ofmentioning
confidence: 99%
“…Pigs exposed to in utero heat stress (IUHS), defined as exposure of the fetus to maternal body temperatures above euthermic levels, are negatively affected throughout postnatal life [20]. For example, IUHS pigs exhibit a chronically elevated core body temperature [21], decreased head and bone weight as a percentage of body weight [22,23], increased circulating triiodothyronine (T 3 ) concentrations and fasting heat production [24], increased fat deposition and circulating insulin concentrations [25], as well as decreased protein accretion [23]. However, little is known about the effects of IUHS in piglets after common production stressors on welfare measures such as the physiological and behavioral stress response.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that IUHS piglets would exhibit a greater physiological and behavioral stress response (increased cortisol; increased aggression and standing, decreased eating, drinking, lying, interaction with straw, and huddling with a pen mate) following weaning and transportation. Additionally, because previous work demonstrated that IUHS pigs have a greater maintenance requirement when compared to IUTN pigs [24], indicators of energy availability and utilization were measured to account for the potential effect of metabolic stress on the physiological and behavioral response to a stressor. We further hypothesized that weaning and transport would lead to a more negative energy balance in IUHS piglets, as compared to their IUTN conspecifics, and this may contribute to reduced welfare.…”
Section: Introductionmentioning
confidence: 99%